Evaluating the Economic Resilience of Horticulture Against Food Inflation: A Price Transmission Analysis from Producers to Consumers of Strategic Commodities Using SP2KP Panel Data - Wartaka; Aisyah (CV. HEI PUBLISHING INDONESIA, 2025)
The economic resilience of Indonesia's horticultural sector is frequently undermined by volatile food inflation and distributional inefficiencies. This study evaluates market resilience and price transmission mechanisms for strategic commodities—specifically chili and shallots—from producer to consumer levels. Utilizing weekly panel data from SP2KP and BAPANAS across 34 provinces (2022–2024), the research incorporates BMKG rainfall anomaly metrics within a Vector Error Correction Model (VECM) and Wald asymmetry tests. The findings confirm a stable long-term cointegration with a moderate weekly price adjustment rate of 24.5%. A pivotal discovery highlights significant asymmetric price transmission, where retail prices respond significantly faster to producer-level increases than to decreases, validating the